FG-Coupled Fixed Point Theorems for Various Contractions in Partially Ordered Metric Spaces - E., Prajisha; P., Shaini (Sarajevo Journal of Mathematics, 2020)
In this paper we introduce FG-coupled fixed point, which is a generalization of coupled fixed point for nonlinear mappings in partially ordered complete metric spaces. We discuss existence and uniqueness theorems of FG-coupled fixed points for different contractive mappings. Our theorems generalizes the results of Gnana Bhaskar and Lakshmikantham [1].